Analisis Pengaruh Kebijakan Utang Dan Beban Pajak Tangguhan Terhadap Kinerja Keuangan Perusahaan Makanan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) 2019 - 2023 - Sanjaya, Anggun; Susyanti, Jeni; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The research aims to determine the influence of debt policy and deffered tax burden on the financial performance of food an beverage companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses a quantitative approach. The sampling technique was carried out using a purposive sampling technique so that the samples obtained were 6 food and beverage companies with a total of 30 observations of data over 5 years. The data collection technique used is documentation. The data analysis technique used in this research is multiple linier regression with SPSS software tools. The research result show that debt policy has a significant effect on financial performance, while deferred tax expenses have no effect on financial performance. Keywords: Debt Policy, Deferred Tax Burden, Financial Performance